Lightning location from induced voltages : an experimental approach [electronic resource] - Siti Rabiatuladawiyah Ibrahim, 1988-, author; Zuraimy Adzis; Fakulti Kejuruteraan Elektrik (2011)
Project Paper (Sarjana Muda) - Universiti Teknologi Malaysia, 2011